Medium modulated oxygen reduction activity of Fe/Co active centre-engrafted electrocatalysts - Kashyap, Varchaswal; Anand, Aljo; Soni, Roby; Sreekumar, Kurungot (ChemElectroChem, 2019)
Iron and cobalt metal atoms are effective active centers for the synthesis of carbon-based noble-metal-free catalysts for the oxygen reduction reaction (ORR) owing to their cost-effective intrinsic activity and tunable properties. Annealing of the active center with the conducting carbon enhances the ORR activity significantly. Herein, we have engrafted Fe and Co active centers in the homemade conducting carbon and the ORR performance has been closely observed under acidic and basic pH conditions to understand the influence of the medium and participating moieties towards the performance. In the half-cell reaction, the onset potential and half-wave potential for ORR are governed by the surface intermediates and concomitantly driven by the adsorption energies of the intermediates over the active centers. The iron and cobalt active center-engrafted carbon catalyst behaves differently in acidic and basic electrolytes owing to the dissociation of the surface intermediates. The iron-based catalyst shows improved onset potential against the cobalt-based one. Similarly, the cobalt-based catalyst shows improved half-wave potential against the iron active-center-grafted catalyst. The combined synergistic effect of the two catalysts is realized in the composition represented as Fe/2Co-N-GVC, where improved onset and half-wave potentials are noted in basic medium. A significant variation in the activity of the catalyst is observed as the medium changes from acidic to basic and the effect is directly associated with the surface adsorption of the intermediates.
Keywords: active centers; half-wave potential; Mechanism; oxygen reduction reaction; transition state

[MoS4](2-)-Intercalated NiCo-layered double hydroxide nanospikes: an efficiently synergized material for urine to direct H-2 generation - Nadeema, Ayasha; Kashyap, Varchaswal; Gururaj, Rakshitha; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2019)
Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental 6 protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2- in its interlayer space. The [MoS4]' insertion as well as its effect on the electronic structure tuning is thoroughly studied via X-ray photoelectron spectroscopy in combination with electrochemical analysis. This insertion induces overall electronic structure tuning of the hydroxide layer in such a way that the designed catalyst exhibited favorable kinetics toward all the required reactions of hydrogen generation. This is why our homemade catalyst, when utilized both as a cathode and anode to fabricate a urea electrolyzer, required a mere X1.37 V cell potential to generate sufficient H2 by reaching the benchmark 10 mA cm-2 in 1 M KOH/0.33 M urea along with long-lasting catalytic efficiency. Other indispensable reason of selecting [MoS4]2- is its high-valent nature making the catalyst highly selective and insensitive to common catalyst-poisoning toxins of urine. This is experimentally supported by performing the real urine electrolysis, where the nanospike-covered Ni foam-based catalyst showed a performance similar to that of synthetic urea, offering its industrial value. Other intuition of selecting [MoS4]2- was to provide a ligand-based mechanism for hydrogen evolution half-cell [hydrogen evolution reaction (HER)] to preclude the HER-competing oxygen reduction. Another crucial point of our work is its potential to avoid the mixing of two explosive product gases, that is, H2 and O-2.
Keywords: hydrogen evolution reaction; Layered double hydroxide; nickel oxyhydroxide; sewage denitrification; urea oxidation reaction; urine/urea electrolysis